Pengaruh Mutasi Kerja, Beban Kerja dan Konflik Kerja terhadap Kinerja Pegawai Dinas Pendidikan dan Kebudayaan Kebupaten Pidie Jaya - Maulida, Maulida; Raihan, Iskandar; Musrizal, Musrizal (Singkite Journal, 2024)
The study aims to analyze factors that improve the performance of employees of the Education and Culture Office, with a study in Pidie Jaya Regency. The factors observed are limited to aspects of work transfers, workload and work conflict. Survey research on 82 employees as respondents, using associative with path analysis. The results of the study found: 1) significantly work transfers, workload and conflict affect employee performance, each amounting to 54.14%, 42.13% and 53.65%. 2) Simultaneously work transfers, workload and work conflict contribute positively by 49,1% to employee performance. 3) There is a causal relationship between the variables of work transfer, workload and work conflict with a moderate category